An Empirical Investigation Of Assembly Line Balancing Techniques And Optimized Implementation Approach For Efficiency Improvements (Global Journals of Research in Engineering, 2012)
The concept of mass production essentially involves the assembly of identical or interchangeable parts of components into the final product at different stages and workstations. The relative advantages and disadvantages of mass or flow production are a matter of concern for any mass production industry. How to design an assembly line starting from the work breakdown structure to the final grouping of tasks at work stations has been discussed in this paper using two commonly used procedures namely the Kilbridge-Wester Heuristic approach and the Helgeson-Birnie Approach. Line Balancing (LB) is a classic, well-researched Operations Research (OR) optimization problem of significant industrial importance. The specific objectives of this paper is to optimize crew size, system utilization, the probability of jobs being completed within a certain time frame and system design costs. These objectives are addressed simultaneously, and the results obtained are compared with those of single-objective approaches.
Keywords: Line Balancing; Kilbridge-Wester Heuristic Approach; Helgeson-Birnie Approach; Optimization